2010
DOI: 10.1118/1.3273063
|View full text |Cite
|
Sign up to set email alerts
|

Coverage optimized planning: Probabilistic treatment planning based on dose coverage histogram criteria

Abstract: This work ͑i͒ proposes a probabilistic treatment planning framework, termed coverage optimized planning ͑COP͒, based on dose coverage histogram ͑DCH͒ criteria; ͑ii͒ describes a concrete proofof-concept implementation of COP within the PINNACLE treatment planning system; and ͑iii͒ for a set of 28 prostate anatomies, compares COP plans generated with this implementation to traditional PTV-based plans generated with planning criteria approximating those in the high dose arm of the Radiation Therapy Oncology Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 27 publications
(39 reference statements)
0
90
0
Order By: Relevance
“…The PTV assumes inherently a uniform response of all points in the PTV, which is an approximation. However, this approximation is consistent with the approximation of assuming everything as water with scaled electronic density for dose calculation, leading to homogeneous dose distributions in the CTV even An elegant way to solve this inconsistency is to use a comprehensive robust optimizer [20,21], which avoids the need of a PTV. Every iteration (or once every  iteration) of the optimizer, dose to medium distribution should be computed taking into account explicitly random and systematic errors.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The PTV assumes inherently a uniform response of all points in the PTV, which is an approximation. However, this approximation is consistent with the approximation of assuming everything as water with scaled electronic density for dose calculation, leading to homogeneous dose distributions in the CTV even An elegant way to solve this inconsistency is to use a comprehensive robust optimizer [20,21], which avoids the need of a PTV. Every iteration (or once every  iteration) of the optimizer, dose to medium distribution should be computed taking into account explicitly random and systematic errors.…”
Section: Discussionmentioning
confidence: 69%
“…1 with the TomoTherapy system and the MC model TomoPen validated elsewhere [19][20][21] instead of our simple analytical approach. The PTV geometry was contoured in the standard cylindrical Virtual Water TM phantom provided with every TomoTherapy unit.…”
Section: Discussionmentioning
confidence: 99%
“…A pDVH corresponding to coverage q is a virtual DVH created by connecting all D v with coverage probability q. The steps to generate a pDVH for a target or CTV can be referred to Gordon et al 14 In this study, a pDVH is a result of "dynamic" DVHs which are different in each virtual treatment course due to the different DVFs sampled from PDFs of PCA model.…”
Section: C1 Coverage Estimation-pdvhmentioning
confidence: 99%
“…Gordon et al (2010) suggested a framework for probabilistic treatment planning where the concept of CTV dose coverage was reused from the formalism of margin design for PTV based planning. By means of dose coverage probability they demonstrated that probabilistic plans yields better target dose coverage compared with margin based plans without compromising organ at risk doses for prostate patients.…”
Section: Introductionmentioning
confidence: 99%
“…Given a priori distributions for the systematic and random uncertainties, a dose volume coverage map (DVCM) can thus be determined by scoring, for every simulated scenario, whether or not a given volume receives at least a certain dose (Gordon et al 2010). A DVCM is the full representation in the dose-volume domain of dose-populationhistograms (van Herk et al 2000, Gordon et al 2007.…”
Section: Introductionmentioning
confidence: 99%